Pengelolaan Jaringan Single Ssid Menggunakan Controller Access Point System Manager (Capsman) Di SMK Labor Binaan FKIP UNRI - Ade Ruslan; Dahliyusmanto Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
To improve the optimization of the internet network, the Vocational High School (SMK) of FKIP UNRI uses the internet network using a wireless network so that all teachers, admin staff, and students can get data from the internet in real-time. SMK Labor has access points with different access point identification names, better known as SSID (Service Set Identifier). Of all the access point devices installed with different SSID names on each device, so that if the user changes buildings, they must reconnect to the SSID in the building. Device configuration is still done manually; therefore, network management impacts the access point management system. The network manager is required to configure the access point devices individually because there is no centralized access point management. To help this success, we need a technology that can manage a network centrally, making it easier to control all wireless access point devices in the network. One example of a wireless device that is often used is a Mikrotik router. Mikrotik has a function to manage a device centrally using the CAPsMAN feature, making it easier for admins to monitor all wireless access point devices contained in the network. With these problems, the author aims to design the management of access points by utilizing the CAPsMAN feature to make it easier for admins to manage and maintain the network at school.Keyword: Single SSID, CAPsMAN, Acess Point, Mikrotik